The Relationship between Foreign Direct Investment from Thailand and Export on the Economic Growth of Laos - Thanet Wattanakul; Tanawat Watchalaanun (Australasian Accounting, Business and Finance Journal, 2017)
This study examines the relationship between Laos’s GDP, Thailand’s direct investment to Laos and Laos’s export to Thailand by using 44 quarters of data from 2005 Q1 to 2015 Q4. All relationships were studied using the vector error correction model (VECM). The results presented long run relationship from Laos’ GDP and Laos’ export to Thailand as well as from Thailand’s direct investment to Laos’s GDP and Laos’s export to Thailand. In the short run, there was only unidirectional relationship from Laos’s GDP to Laos’s exports to Thailand. This study indicates that Laos’s exporters receive benefits from Thailand’s direct investment contribution to accelerate economic growth in the short term. Therefore, Laos’s government should distribute income from the exporters to other economy sectors or spread the types of export goods into a larger range.
Keywords: FDI; Export; Economic Growth; VECM